2018
DOI: 10.4067/s0718-95162018005003302
|View full text |Cite
|
Sign up to set email alerts
|

Early responses to manganese (Mn) excess and its relation to antioxidant performance and organic acid exudation in barley cultivars

Abstract: Manganese (Mn) is an essential micronutrient for plants, and is necessary for biochemical and physiological processes. The objective of this research was to determine the early responses to Mn excess and its relation to antioxidant performance mechanisms and organic acid exudation in commercial barley cultivars. We determined early responses to Mn excess in four barley cultivars (Barke, Tatoo, Scarlett, Sebastian), which were subjected to increasing Mn concentrations (2.4-150-350-750-1500 µM Mn), pH 4.8, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The opposite position between the parameters of root growth and phytochemicals clearly exhibited the negative correlation, which was also observed in Lactuca sativa [ 65 ] and Hordeum vulgare [ 66 ]. The negative correlations may be indirectly resulted from the solidification states of the culture.…”
Section: Resultsmentioning
confidence: 87%
“…The opposite position between the parameters of root growth and phytochemicals clearly exhibited the negative correlation, which was also observed in Lactuca sativa [ 65 ] and Hordeum vulgare [ 66 ]. The negative correlations may be indirectly resulted from the solidification states of the culture.…”
Section: Resultsmentioning
confidence: 87%
“…In contrast, other studies shown that the antioxidant system decreases its activity due to the effects of Mn [19] and these contrasting antioxidant responses when facing excess Mn are directly influenced by Mn resistance and sensitivity mechanisms in plants [18]. Millaleo et al [18] on example of four barley cultivars showed that Mnresistant varieties increased AOA and sensitive cultivars decreased AOA. According to these observations, all barley varieties studied by us are considered as potentially resistant to manganese ions, but differ in resistance to iron ions: cv.…”
Section: Discussionmentioning
confidence: 93%
“…In the case of manganese, an increase in antioxidant activity was observed in all cultivars studied; and in iron influence, a significant change was observed only in three cultivars, of which two cultivars had an increase in this parameter. Since it is known that antioxidant performance such as antioxidant activity (AOA) and antioxidant enzymes such as superoxide dismutase (SOD) were activated in presence of excess Mn [18], probably in different barley genotypes disorders are associated with different biochemical reactions (increase in synthesis of enzymes, secondary metabolites, lipid peroxidation of membranes). In contrast, other studies shown that the antioxidant system decreases its activity due to the effects of Mn [19] and these contrasting antioxidant responses when facing excess Mn are directly influenced by Mn resistance and sensitivity mechanisms in plants [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These chemicals were used as chelating agents to reduce metal toxicity in plants [113]. In the case of certain variable-valence metals, their solubility and phytotoxicity are often influenced by their redox status [114,115]. Therefore, plants have the capacity to oxidize metals including Mn by releasing oxygen and oxides to reduce their toxic effects [116].…”
Section: Soil Metal Stress Relieved By Root Exudatesmentioning
confidence: 99%